(untitled) (Cambridge, 2004)
This textbook furnishes a comprehensive survey of current language issues in the U.S., exploring the nature of language variation in the United States and its social, historical and political significance. The book is divided into three sections: Part I, American English; Part II, Other Language Varieties; and Part III, The Sociolinguistic Situation in the U.S.A.
Keywords: United States,Hoa Kỳ; Languages,Ngôn ngữ